1985
DOI: 10.1099/0022-1317-66-1-55
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Bovine Cytomegalovirus Genome Structure: Cloning and Mapping of the Monomeric Polyrepetitive DNA Unit, and Comparison of European and American Strains

Abstract: SUMMARYThe genome of bovine cytomegalovirus (BCMV) strain 66-P-347 consists of doublestranded, linear DNA with a size of 144 + 6 kb. It contains polyrepetitive DNA (prDNA) segments like five other BCMV strains. The restriction patterns of the prDNA of all six strains are very similar and indicate that monomeric prDNA units are either 1950 bp (class I and Ia), 2350 bp (class II) or 2750 bp (class III) in size. The complete unit sequence of strain 66-P-347 (class II) was cloned in bacteriophage vector M13mp7 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
55
0

Year Published

1988
1988
2000
2000

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(59 citation statements)
references
References 16 publications
4
55
0
Order By: Relevance
“…Gammaherpesviruses are lymphotropic viruses represented by Epstein-Barr virus (EBV) and Kaposi's sarcoma-associated herpesvirus (HHV-8). The genome of BHV-4 is a double-stranded 145-kb DNA molecule consisting of a 110-kb central unique coding sequence, called L-DNA, flanked by two stretches of tandem repeats (24,25). These stretches are designated polyrepetitive DNA (prDNA).…”
mentioning
confidence: 99%
“…Gammaherpesviruses are lymphotropic viruses represented by Epstein-Barr virus (EBV) and Kaposi's sarcoma-associated herpesvirus (HHV-8). The genome of BHV-4 is a double-stranded 145-kb DNA molecule consisting of a 110-kb central unique coding sequence, called L-DNA, flanked by two stretches of tandem repeats (24,25). These stretches are designated polyrepetitive DNA (prDNA).…”
mentioning
confidence: 99%
“…BHV-4 strain 66-p-347 was propagated in Georgia bovine kidney (GBK) cells and BHV-4 particles were prepared from the supernatant of infected cells. Virus DNA isolation has been described previously (Ehlers et al, 1985).…”
Section: Methodsmentioning
confidence: 99%
“…These stretches have been designated polyrepetitive DNA (prDNA). Using a prDNA unit as a molecular probe, we have (i) identified the genomic termini of BHV-4 as well as restriction fragments representing the junctions between prDNA and unique DNA and (ii) demonstrated that the frequencies of prDNA units at both genomic termini vary between individual molecules of a strain (Ehlers et al, 1985). For the investigated BHV-4 strain 66-p-347 (Storz, Author for correspondence : Michael Goltz.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Amid this variety, one structural pattern is especially remarkable in that it embodies the extremes of base composition and sequence repetition currently recognized for the herpesvirus group as a whole. Originally discovered in herpesvirus saimiri (Bornkamm et al, 1976), similar genome structures have since been found in other New World primate herpesviruses (reviewed by Fleckenstein & Desrosiers, 1982), several bovine herpesviruses (Ehlers et al, 1985), and two independently isolated cottontail rabbit herpesviruses, herpesvirus sylvilagus (Medveczky et al, 1984;see, however, Rouhandeh & Cohrs, 1987) and CTHV (J. Cebrian et al, personal communication).…”
Section: Introductionmentioning
confidence: 99%